Beam loading compensation of standing wave linac with off-crest acceleration. Issue 1 (1st January 2023) - Kuriki, M; Konno, S; Tajino, H; Liptak, Z; Takahashi, T; Fukuda, M; Omori, T; Seimiya, Y; Urakawa, J; Yokoya, K; Kashiwagi, S
Abstract: In E-Driven positron source of ILC, the generated positron is captured by a standing wave cavity. Because the deceleration capture method is employed, the positron is off-crest over the linac. Because the beam-loading is expected to be more than 1A in a multi-bunch format, the compensation is essential to obtain uniform intensity over the pulse. A conventional method for the compensation controlling the timing doesn't work because RF and Beam induced field are in different phase. In this manuscript, we discuss the compensation with the off-crest acceleration case. A simple phase modulation on the input RF is a solution.